The factors that influence consumers' willingness to disclose personal information to social networking site providers. A case study of the Vietnamese using Facebook. - Vu, Phuong Anh (2019)
The goal of this study is to examine how different factors influence the consumers’ willingness to disclose personal information to the SNS providers. The study focused on investigating the privacy paradox between the inhibitor as the perceived risk and the driver as the perceived benefits. It later investigated the other three constructs namely social influence, relational factor and contextual factor to understand whether they have an influence on the voluntary disclosing behaviour of online users. The goal was achieved by addressing three research questions: i) The information privacy concern regarding loss of face and loss of privacy (Barnett, 2004; Dahl et al., 2001; Malhotra et al., 2004); ii) The drivers of information sharing regarding social influence (Taylor and Todd, 1995), perceived benefits, perceived trust (Malhotra et al., 2004; Barnett, 2004) and type of information (Phelps et al., 2000); and iii) The benefit expectations of information sharing regarding enjoyment (Moon and Kim, 2001; Ellison et al., 2007), convenience in building relationships (Ellison et al., 2007; Krasnova et al., 2010) and compensation (Premazzi et al., 2010). This research was designed as a quasi-experimental questionnaire that allowed both the measuring of the main constructs – perceived risk, perceived benefit, social influence, and relational factor – and the testing of two conditions in the contextual factor – less sensitive and highly-sensitive information. This proposed framework was based on the conceptualisation of the constructs identified in prior literature that research about self-disclosure behaviour. With the gap in previous literature, the study attempts to understand the behaviour of consumers in developing countries. The approach was supported by analyses that verified the arguments by other academics and supported the hypotheses of key concepts (H1 and H2). The findings provided support of certain concepts that are positively related to the intention to disclose information. It demonstrated that convenience in building relationships is the most dominant factor in triggering information disclosure, followed by enjoyment, trust in SNS providers and less sensitive information. Meanwhile, it noted the factors that have little impact (social influence) or adverse impact (loss of face and privacy) on the information disclosure. The counterintuitive findings of previous research were also added to compare with the results of the hypotheses. Hence, the research pinpointed the theoretical, practical and ethical implications, along with the limitation and future direction to further expand the extent of knowledge regarding the information disclosure on SNS. Therefore, practitioners and commercial organisations can adopt these insights to tailor their strategies in order to reduce privacy concern and maximise the disclosure behaviour of individuals in developing countries.